Mutagenic potential of fried and boiled “Keropok lekor”: a study using the Ames test - Abdullah, Rozaini; Shafie, Siti Raihanah; Engku Puteri Nurfaranajieha (Environmental and Occupational Health Society, 2024)
“Keropok lekor”, a traditional Malaysian fish sausage, is widely consumed, yet its mutagenic potential has not been thoroughly investigated. Objective: This study evaluated the mutagenic activity of keropok lekor samples. Methodology: Samples were analysed using the Ames test with Salmonella typhimurium strains TA98 and TA100, with and without S9 metabolic activation. Boiled “keropok lekor” and fried samples variants were tested at concentrations of 1.0, 2.0, and 4.0 mg/mL. Results: The fried samples demonstrated significant mutagenicity in the absence of metabolic activation, with revertant colony counts exceeding the two-fold threshold of solvent controls at higher concentrations. In contrast, the boiled samples showed lower mutagenic activity, suggesting that frying may increase mutagenicity. Furthermore, while the addition of S9 metabolic activation reduced mutagenic responses, a dose-response relationship was noted in both variants, indicating a concentration-dependent effect. These findings highlight the potential health risks associated with frequent consumption of fried “keropok lekor” and emphasize the need to evaluate traditional foods for genotoxic risks.